Pengaruh Lama Penyimpanan Menggunakan Media Arang Sekam Padi Terhadap Perkecambahan Benih Kakao Hibrida - Ayu, Elma Kusuma; Fatimah, Titien; Salim, Abdurrahman (Agropross : National Conference Proceedings of Agriculture, 2023)
The Indonesian cocoa plantation business is dominated by the provinces of Sulawesi and Sumatra with the condition of the plants entering an unproductive period. The implementation of replanting is the main focus in 2022 by the Cocoa Sustainability Partnership through the provision of planting materials in the form of superior seeds from Puslitkoka Jember. Regional differences make seed delivery take a long time so that the seeds are in their shelf life. Storing cocoa seeds using a storage medium in the form of husk charcoal is carried out in order to maintain their water content in order to produce maximum germination when the seeds are received by consumers so they can grow well. This research was conducted at the Jember State Polytechnic in September-October 2022 using a factorial randomized design consisting of two factors. The first factor was the length of storage of cocoa seeds which consisted of 0 days (L0), 4 days (L1), 8 days (L2), 12 days (L3). The second factor was the type of cocoa clones used consisting of ICCRI 06 H (K1) and ICCRI 08 H (K2). The results showed that seeds with a long storage time of L1 were able to maintain maximum water content and germination after L0, while storage times of L2 and L3 decreased in water content which resulted in low germination. The longer the seeds are in the travel shelf life, the germination of the seeds decreases. Meanwhile, the cocoa clones in this study did not show any interaction